Risk factors associated with tonsillar hypertrophy in sickle cell patients followed at the Centre for Mixed Medicine and Sickle Cell Anaemia in Kinshasa - Yalombe, Honoré Ngoyi; kalala, hilaire kabala; Ntumba, Sarah; Tshingamb, Yasmine Kamin; Nyembue, Dieudonné Tshipukane (Orapuh Journal, 2025)
Introduction Sickle cell disease is the most common genetic disorder worldwide, primarily affecting individuals of African, Mediterranean, and Asian descent. Previous studies have reported that patients with sickle cell disease are predisposed to tonsillar hypertrophy as a result of compensatory immune responses to functional asplenia and recurrent infections. Purpose The main objective of this study was to determine the frequency of tonsillar hypertrophy in sickle cell patients followed at our centre and to identify the associated risk factors. Methods This was a cross-sectional analytical study conducted at the Centre for Mixed Medicine and Sickle Cell Anaemia (CMMASS), Kinshasa, from September 2022 to February 2023. The sample comprised homozygous SS sickle cell patients aged six years and above who were followed up at CMMASS. The size of the palatine tonsils was assessed according to Friedman’s criteria. Data were analysed using IBM Statistical Package for the Social Sciences (SPSS) version 26.0. Associations between variables were tested using the chi-square test, with statistical significance set at p < 0.05. Results A total of 123 patients with sickle cell disease participated in the study, with a median age of 15 years (range: 6–50 years). Females accounted for 58.5% of participants. The prevalence of tonsillar hypertrophy was 57.7%. Treatment without hydroxyurea (adjusted OR = 10.53 [1.74–63.59]; p = 0.010), presence of jaundice (adjusted OR = 4.21 [1.33–13.39]; p = 0.015), and haemoglobin ≤ 7.9 g/dL (adjusted OR = 7.55 [2.85–19.99]; p = 0.001) were identified as factors significantly associated with tonsillar hypertrophy among sickle cell patients. Conclusions Tonsillar hypertrophy is common among sickle cell patients in our setting. Addressing the associated risk factors identified in this study could help reduce its frequency.